A framework for 'configuring participation' in living labs. (14th November 2022) - Akasaka, Fumiya; Mitake, Yuya; Watanabe, Kentaro; Shimomura, Yoshiki
Abstract: In recent years, 'living lab (LL)', a design approach that actively involves users as partners from the early stage of the design process, has been attracting much attention. Compared with the traditional participatory design or co-design approaches, one of the distinctive features of the LL approach is that the process of and opportunity for user participation tends to be long-term and complex. Thus, LL practitioners must appropriately plan and design effective integration of user participation into the design process to promote co-creation with users. In other words, LL practitioners are required to 'configure user participation' for the effective promotion of co-creation. However, to date, the knowledge on how to properly configure long-term and complex user participation in LLs has not been systematically clarified, nor have its methodologies been developed. This study develops a novel framework for configuring user participation in LLs. Through a literature review and analysis on LL case studies, we identified the 11 key elements in five categories that should be considered while configuring user participation in LLs. Furthermore, on the basis of the identified elements, we developed a novel framework for configuring user participation in LLs, which is called the participation blueprint. We have demonstrated its use and have also discussed its theoretical and practical contributions to the LL and co-design research community.